Common variants at Bin1 are associated with sporadic Alzheimer's disease in the Han Chinese population. (February 2015) - Li, Hong-Lei; Yang, Ping; Liu, Zhi-Jun; Sun, Yi-Min; Lu, Shen-Ji; Tao, Qing-Qing; Guo, Qi-Hao; Wu, Zhi-Ying
<x xml:space="preserve">Abstract</x> Objectives Recent genome-wide association studies identified bridging integrator 1 (Bin1) to be associated with sporadic Alzheimer's disease (SAD). To clarify the relevance of Bin1 as a genetic determinant of AD, we analyzed its association in a Han Chinese population from the South East part of mainland China. Methods This study investigated 427 SAD patients and 451 unrelated age-matched and sex-matched healthy controls. Two single nucleotide polymorphisms (rs7561528 and rs744373) adjacent to Bin1 that emerged from previous genome-wide association studies were genotyped using the MassARRAY Analyzer 4 Sequenom platform. Results As expected, the genotype distribution of rs7561528 was significantly different between the SAD group and the controls, with more AG in controls [odds ratio (OR) 0.605, 95% confidence interval (CI) 0.429–0.854, P=0.004], and the difference increased using an additive genetic model (OR 0.593, 95% CI 0.425–0.828, P=0.002). However, we did not observe a difference in the genotype distribution of the rs744373 between the SAD and the control group (OR 1.189, 95% CI 0.809–1.747, P=0.378). Conclusions To the best of our knowledge, our study is the first to confirm the association of the variant rs7561528 adjacent to Bin1 with SAD in a Han Chinese Population.